First analysis of the physicochemical composition of the waters of Lake Kankossa, Mauritania - Moctar, HABIBY El; DICK, Brahim Ahmed; SIDIHAMOUD, Fatimetou Salma; SLIMANE, Hamid; BELGHYTI, Driss (Edelweiss Applied Science and Technology, 2025)
In many countries, population growth, rapid urbanization, industrialization, and the irrational use of fertilizers and pesticides are severely disrupting natural environments, leading to an imbalance in ecosystems and generating physico-chemical and biological pollutants in receiving aquatic environments, and changing their uses, such as drinking water collection, livestock watering, and bathing. The objective of our study is to analyze the spatial and temporal variations in the physicochemical properties of Lake Kankossa waters. The study is based on four sampling campaigns conducted over a two-year period, between 2017 and 2021, covering seven representative sampling points: Exploitation, ElVak, ElHakem, Essak, Harth Ewlad Emin, ElHachya, and ElBir. The parameters analyzed are: pH, temperature, turbidity, suspended solids, conductivity, major ions, calcium, magnesium, sodium, potassium, nitrate, nitrite, sulfate, and chloride. Recorded temperatures range from 24 to 25.1 °C in March and October, and from 32 to 38.7°C in September and April. The pH is slightly neutral to very alkaline, varying between 7.28 and 10.93, sometimes reaching 11. Recorded conductivity values fluctuate between 158 and 460 μS/cm during humid periods and decrease to between 210 and 377 μS/cm during dry periods. Average turbidity and suspended solids (SS) levels peak during winter (134–148 mg/L and 317.5 NTU).